Food and beverage flavour pairing: A critical review of the literature - Spence, C (Elsevier, 2020)
The recent explosion of interest in the topic of flavour pairing has been driven, at least in part, by the now-discredited food-pairing hypothesis, along with the emergence of the new field of computational gastronomy. Many chefs, sommeliers, mixologists, and drinks brands, not to mention a few food brands, have become increasingly interested in moving the discussions that they have with their consumers beyond the traditional focus solely on food and wine pairings. Here, two key approaches to pairing that might help to explain/justify those food and beverage combinations that the consumer is likely to appreciate are outlined. Historically-speaking, many conventional pairings emerged naturally from cultural/geographical matches, presumably internalized as semantic knowledge amongst consumers. In this review, such conventional pairings are framed as but one example of a cognitive/intellectual food-beverage strategy. The alternative approach to pairing that has become increasingly popular in recent years involves experts/commentators making recommendations based on the perceptual relationship, or interaction, between the component stimuli, be it one of perceived similarity, contrast, harmony, emergence, or modulation (either suppression or enhancement). Physicochemical accounts of pairing, based on the presence of shared flavour molecules (e.g., aromatic volatiles) in the to-be-combined flavours or ingredients, have also gained in popularity. Here, though, the latter approach is framed as an ultimately unsuccessful attempt to predict matches based on perceived similarity. This review summarizes the available evidence concerning food-beverage pairing and proposes a new dichotomy between intellectual/cognitive and perceptual pairing principles in the case of food-beverage matching.